2022
DOI: 10.1136/jmedgenet-2021-107971
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping cortical malformations in patients with pathogenic variants inGRIN1andGRIN2B

Abstract: BackgroundMalformations of cortical development (MCDs) have been reported in a subset of patients with pathogenic heterozygous variants in GRIN1 or GRIN2B, genes which encode for subunits of the N-methyl-D-aspartate receptor (NMDAR). The aim of this study was to further define the phenotypic spectrum of NMDAR-related MCDs.MethodsWe report the clinical, radiological and molecular features of 7 new patients and review data on 18 previously reported individuals with NMDAR-related MCDs. Neuropathological findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…(Met818Thr) variant, with the GRIN2B c.2452A>C/p. (Met818Thr) variant being previously reported in patients with DEE/IESS phenotype with and without cortical malformations 53 and DD without epilepsy. 54 Functional studies suggested possible GoF 53,55 and in vitro studies and animal models suggested a potential therapeutic response to memantine.…”
Section: Dee-related To Receptors or Transporters Disordersmentioning
confidence: 85%
See 1 more Smart Citation
“…(Met818Thr) variant, with the GRIN2B c.2452A>C/p. (Met818Thr) variant being previously reported in patients with DEE/IESS phenotype with and without cortical malformations 53 and DD without epilepsy. 54 Functional studies suggested possible GoF 53,55 and in vitro studies and animal models suggested a potential therapeutic response to memantine.…”
Section: Dee-related To Receptors or Transporters Disordersmentioning
confidence: 85%
“…(Met818Thr) variant being previously reported in patients with DEE/IESS phenotype with and without cortical malformations 53 and DD without epilepsy 54 . Functional studies suggested possible GoF 53,55 and in vitro studies and animal models suggested a potential therapeutic response to memantine 54,56 . However, evidence of a significant favorable response to memantine in patients with GoF variants have been conflicting 57 .…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 More than 350 variants of the GluN1 subunit have been identified. 10 The variants mostly occur within the ATDs, LBDs, and TMDs 8 , 11 , 12 and can result in either gain‐ or loss‐of‐function molecular phenotypes. 10 , 11 , 12 Here, we report three newly identified variants of the GluN1 subunit, which we expressed on the GluN1‐3b splice isoform for functional analysis.…”
Section: Introductionmentioning
confidence: 99%
“… 10 The variants mostly occur within the ATDs, LBDs, and TMDs 8 , 11 , 12 and can result in either gain‐ or loss‐of‐function molecular phenotypes. 10 , 11 , 12 Here, we report three newly identified variants of the GluN1 subunit, which we expressed on the GluN1‐3b splice isoform for functional analysis. The missense p. Ile148Val variant is absent from any databases and occurs within the LBD of the receptor.…”
Section: Introductionmentioning
confidence: 99%